(untitled) (Revista de Artes Marciales Asiáticas, 2021)
This study aimed to understand the experiences of professional mixed martial arts (MMA) fighters in the psychological transition between fight and violence, based on their own reports. Semi-structured interviews were conducted with an intentional sample of five participants and their analysis was carried out from a phenomenological perspective. The intentional crossing of experiences allowed the identification of five categories: maintaining focus vs. losing your head; maintenance of the technique vs. loss of the technique; feeling good vs. embarrassment; desire to test yourself vs. aggression; desirable retaliation vs. disproportionate retaliation. The results of this study indicate that the intensification of the combative exchange that leads to the transition from the first to the second item of each category is the key element in the subjective transition between fight and violence.